Inflammation Induced by Platelet-Activating Viperid Snake Venoms: Perspectives on Thromboinflammation - Teixeira, Catarina; Fernandes, Cristina Maria; Leiguez, Elbio; Chudzinski-Tavassi, Ana Marisa (Frontiers in Immunology, 2019)
Envenomation by viperid snakes is characterized by systemic thrombotic syndrome and prominent local inflammation. To date, the mechanisms underlying inflammation and blood coagulation induced by Viperidae venoms have been viewed as distinct processes. However, studies on the mechanisms involved in these processes have revealed several factors and signaling molecules that simultaneously act in both the innate immune and hemostatic systems, suggesting an overlap between both systems during viper envenomation. Moreover, distinct classes of venom toxins involved in these effects have also been identified. However, the interplay between inflammation and hemostatic alterations, referred as to thromboinflammation, has never been addressed in the investigation of viper envenomation. Considering that platelets are important targets of viper snake venoms and are critical for the process of thromboinflammation, in this review, we summarize the inflammatory effects and mechanisms induced by viper snake venoms, particularly from the Bothrops genus, which strongly activate platelet functions and highlight selected venom components (metalloproteases and C-type lectins) that both stimulate platelet functions and exhibit pro-inflammatory activities, thus providing insights into the possible role(s) of thromboinflammation in viper envenomation.